The hand that first held mine [book club bag] - O'Farrell, Maggie, 1972- (Mariner Books, Houghton Mifflin Harcourt, 2011)
Fifty years after a reporter of genteel origins becomes a single mother, London painter Elina navigates the first weeks of motherhood after surviving a dangerous labor and learns that her life is disconcertingly linked to the woman from the past.